1992
DOI: 10.1530/jrf.0.0960641
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and insulin-like growth factor I in follicular fluid after induction of ovulation in women undergoing in vitro fertilization

Abstract: This study was undertaken to evaluate the relationship between concentrations of insulin and insulin-like growth factor I (IGF-I) in follicular fluid and fertilization and cleavage of human oocytes fertilized in vitro. The concentration of oestradiol, progesterone, luteinizing hormone, follicle-stimulating hormone, testosterone, insulin and IGF-I was determined in 36 follicular fluids, free of visible blood contamination and containing mature oocyte-corona-cumulus complexes, obtained from 12 women undergoing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Two earlier studies,[2627] had linked FF IGF-1 with follicular development and oocyte maturation but found no significant correlation with embryo cleavage rates. Bencomo et al (2006)[28] reported a dose dependent decrease in the rate of apoptosis of human granulosa lutein (GL) cells and embryo fragmentation rates.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Two earlier studies,[2627] had linked FF IGF-1 with follicular development and oocyte maturation but found no significant correlation with embryo cleavage rates. Bencomo et al (2006)[28] reported a dose dependent decrease in the rate of apoptosis of human granulosa lutein (GL) cells and embryo fragmentation rates.…”
Section: Discussionmentioning
confidence: 97%
“…[192021] Human studies with IGF-1 have mostly employed in vitro cell culture techniques,[222324] with exogenous supplementation instead of its estimation in in situ sources like FF. [25] A definitive role of IGF-1 in FF has not yet been established or is poorly understood with conflicting reports,[2627282930] on its predictive values. Moreover, no approach has yet been made to directly correlate FF IGF-1 with embryo quality.…”
Section: Introductionmentioning
confidence: 99%
“…A study on FF markers to predict an implantation potential of embryos showed that mean intrafollicular concentrations of IGF-I were significantly higher in patients who became pregnant versus those who failed to establish a pregnancy [16] . Moreover, higher FF IGF-I concentrations were associated with mature oocytes that would be fertilized and cleaved, which might indicate an important role for IGF-I in the mature follicle [20] . In addition, FF IGF-I concentrations were found to be significantly correlated with increasing follicular size and were significantly higher in follicles with mature oocytes than in follicles with atretic oocytes [21] .…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, mean FF concentrations of IGF-I and IGFBP-1 were significantly lower in those with a reduced ovarian reserve with no change in E 2 or IGF-II levels [18] . The ratio of IGF-I/ IGFBP-1 in FF was found to be correlated with pregnancy rates, indicating that both IGF-I and IGFBP-1 could be used as indicators of oocyte quality and oocyte maturity [17,[19][20][21] .…”
mentioning
confidence: 97%
“…The role of insulin in synthesis of oxytocin in granulosa cells has been studied in recent years [17]. However, very little is known about the relationship between concentrations of insulin and oxytocin in follicular fluid and parameters of oocyte quality and roles of these hormones in the fertilization process [20].…”
Section: A4mentioning
confidence: 99%